Integrated Traditional Chinese Medicine Improves Functional Outcome in Acute Ischemic Stroke: From Clinic to Mechanism Exploration With Gut Microbiota - Guo, Qian; Ni, Can; Li, Linjing; Li, Mo; Jiang, Xiaoqing; Gao, Li; Zhu, Huaiqiu; Song, Juexian (Frontiers in Cellular and Infection Microbiology, 2022)
As a life-threatening disease, stroke is the leading cause of death and also induces adult disability worldwide. To investigate the efficacy of the integrated traditional Chinese medicine (ITCM) on the therapeutic effects of acute ischemic stroke (AIS) patients, we enrolled 26 patients in the ITCM [Tanhuo decoction (THD) + Western medicine (WM)] group and 23 in the WM group. Thirty healthy people were also included in the healthy control (HC) group. ITCM achieved better functional outcomes than WM, including significant reduction of the phlegm-heat syndrome and neurological impairment, and improvement of ability. These facts were observed in different pretreatment gut enterotypes. In this paper, we collected the stool samples of all participants and analyzed the 16S rRNA sequence data of the gut microbiota. We identified two enterotypes (Type-A and Type-B) of the gut microbial community in AIS samples before treatment. Compared to Type-B, Type-A was characterized by a high proportion of Bacteroides, relatively high diversity, and severe functional damage. In the ITCM treatment group, we observed better clinical efficacy and positive alterations in microbial diversity and beneficial bacterial abundance, and the effect of approaching healthy people’s gut microbiota, regardless of gut enterotypes identified in pretreatment. Furthermore, we detected several gut microbiota as potential therapeutic targets of ITCM treatment by analyzing the correlations between bacterial abundance alterations and functional outcomes, where Dorea with the strongest correlation was known to produce anti-inflammatory metabolite and negatively linked to trimethylamine-N-oxide (TMAO), a biomarker of AIS. This study analyzed clinical and gut microbial data and revealed the possibility of a broad application independent of the enterotypes, as well as the therapeutic targets of the ITCM in treating AIS patients with phlegm-heat syndrome.